Bactérias promotoras de crescimento de plantas na cultura do milho submetido a diferentes níveis de pH do solo - Inagaki, Adriano Mitio (2014)
The aim of this study was to determine the population of diazotrophic bacteria in the roots of corn plants, and soil cultivation of these plants, as well as evaluating the initial development as a function of seed inoculation with Azospirillum brasilense and Herbaspirillum seropedicae and levels of acidic pH of the soil, no added nitrogen fertilizer. Experiment was conducted in a greenhouse in pots of 13 dm3 of soil, with the hybrid corn 30F53H. For the evaluation of the initial development we used a randomized block design in a 3x4 factorial design, with one factor levels of soil acidity [pH (CaCl2) of 4,5; 5,0 and 5,5] and another the seed inoculation : no inoculation; A. brasilense (Ab-V5), H. seropedicae (SmR1) and the association of strains Ab-V5+SmR1. To measure the population of diazotrophs expressed in colony forming units (CFU), using the design was randomized blocks in a factorial 12 x 2 x 2 and four blocks, totaling 48 experimental plots. The first factor was composed of twelve combinations using inoculation with A. brasilense and H. seropedicae and different levels of soil pH; The second factor, the time of sampling at 15 and 41 days after sowing (DAS). And the third factor, the culture media, and NFb Lactate and Malate used the growth of bacteria and enumeration of CFU. Inoculation was performed via seed 12 hours before sowing, with a volume of 4 mL concentration of 107 CFU mL-1 for a thousand seeds. The evaluations were done at 15 and 41 DAS, and used the method of the most probable number (MPN) for the estimation of bacterial population, in addition to evaluation of plant height, dry weight of root, stem, leaf and total area leaf, stem diameter, SPAD index, foliar N, P, and K, and measurements of gas exchange A, gs , E and EUA. Soil acidity negatively influenced plant height, root dry matter, stem diameter, SPAD index, leaf P concentration, rate of net CO2 assimilation, stomatal conductance, transpiration and water use efficiency. Maize plants grown in soil with pH 4,5 had higher leaf P content regardless of inoculation, indicating probable solubilization of phosphorus. Inoculation of growth promoting bacteria from plants (GPBPs) in maize (30F53H), showed higher accumulation of leaf N, regardless of soil pH, increase in leaf area, SPAD index and stem diameter, and did not influence the accumulation of matter dried plants. The population of bacteria found in soil and roots of maize, regardless of seed inoculation and soil pH levels, showed elevated levels. The inoculation with strains of A. brasilense and H. seropedicae showed no preference for colonization in the soil or in the roots of corn plants. Samples taken at 41 DAS resulted in greater population of diazotrophs when comparing the collection held at 15 DAS. The different levels of soil pH and isolated or in combination, GPBPs did not influence the population of colonies of bacteria detected in the media NFB Lactate and Malate used. The BPCPs proved promising when compared to the control treatment and subjected to stress conditions of soil acidity and nitrogen deficiency, indicating possible biological nitrogen fixation and solubilization of phosphorus. Although the number of CFU of bacteria present is higher in roots and soil, momentary gas exchange measurements recorded, showed no difference between treatments for both inoculation of seeds on the soil pH